Replacement of heme by soluble guanylate cyclase (sGC) activators abolishes heme-nitric oxide/oxygen (H-NOX) domain structural plasticity - Argyriou, Aikaterini I.; Makrynitsa, Garyfallia I.; Dalkas, Georgios; Georgopoulou, Dimitra A.; Salagiannis, Konstantinos; Vazoura, Vassiliki; Papapetropoulos, Andreas; Topouzis, Stavros; Spyroulias, Georgios A. (Current research in structural biology, 2021)
The gasotransmitter nitric oxide (NO) is a critical endogenous regulator of homeostasis, in major part via the generation of cGMP (cyclic guanosine monophosphate) from GTP (guanosine triphosphate) by NO's main physiological receptor, the soluble guanylate cyclase (sGC). sGC is a heterodimer, composed of an α1 and a β1 subunit, of which the latter contains the heme-nitric oxide/oxygen (H-NOX) domain, responsible for NO recognition, binding and signal initiation. The NO/sGC/cGMP axis is dysfunctional in a variety of diseases, including hypertension and heart failure, especially since oxidative stress results in heme oxidation, sGC unresponsiveness to NO and subsequent degradation. As a central player in this axis, sGC is the focus of intense research efforts aiming to develop therapeutic molecules that enhance its activity. A class of drugs named sGC “activators” aim to replace the oxidized heme of the H-NOX domain, thus stabilizing the enzyme and restoring its activity. Although numerous studies outline the pharmacology and binding behavior of these compounds, the static 3D models available so far do not allow a satisfactory understanding of the structural basis of sGC's activation mechanism by these drugs. Herein, application NMR describes different conformational states during the replacement of the heme by a sGC activators. We show that the two sGC activators (BAY 58-2667 and BAY 60-2770) significantly decrease the conformational plasticity of the recombinant H-NOX protein domain of Nostoc sp. cyanobacterium, rendering it a lot more rigid compared to the heme-occupied H-NOX. NMR methodology also reveals, for the first time, a surprising bi-directional competition between reduced heme and these compounds, pointing to a highly dynamic regulation of the H-NOX domain. This competitive, bi-directional mode of interaction is also confirmed by monitoring cGMP generation in A7r5 vascular smooth muscle cells by these activators. We show that, surprisingly, heme's redox state impacts differently the bioactivity of these two structurally similar compounds. In all, by NMR-based and functional approaches we contribute unique experimental insight into the dynamic interaction of sGC activators with the H-NOX domain and its dependence on the heme redox status, with the ultimate goal to permit a better design of such therapeutically important molecules. [Display omitted] •When the heme of Ns H-NOX is replaced by the sGC activators, the protein’s flexibility is significantly reduced.•Heme causes the conformational exchange of Ns H-NOX, as many residues around the heme adopt invisible conformation.•L-ascorbate prevents the proper action of BAY 58-2667 and BAY 60-2770 from forming a stable complex with the Ns H-NOX.•In A7r5 cells, L-ascorbate does not affect cGMP formation induced by BAY 58-2667 and it inhibits the effect of BAY 60-2770.•BAY molecules act on the H-NOX or the sGC in a bi-directional way, depending on the redox state of the heme.